NEUROLOGICAL PROFILE IN PATIENTS WITH STROKE: POSITIVE AND NEGATIVE FOR SARS-COV-2 INFECTION - A RETROSPECTIVE OBSERVATIONAL STUDY - Petrovska, Monika; Matveeva, Niki (Journal of Morphological Sciences; Vol 8 No 2 (2025): JMS, 2025)
Sars-CoV-2 infection is linked to an increased risk of both ischemic and hemorrhagic strokes, influenced by factors such as inflammation, coagulopathy, and endothelial dysfunction.  This study aimed to evaluate the prevalence of different types of stroke, assess the severity of initial neurological deficits using the National Institutes of Health Stroke Scale (NIHSS), and examine neurological disability or dependence on daily activities after treatment using the Modified Rankin Scale (MRS) in patients both positive and negative for Sars-CoV-2. Additionally, the study sought to compare the types of strokes and the degree of neurological deficits and disabilities between these two groups. This retrospective observational cohort study included 91 stroke patients hospitalized in the Department of Neuropsychiatry at the General Hospital of Ohrid during the period from January 1, 2021, to December 31, 2021, which corresponds to the post-COVID period. The findings revealed that Sars-CoV-2 positive patients were generally younger than those who tested negative. Most patients admitted with an initial diagnosis of stroke were classified within the ischemic stroke group, regardless of their COVID-19 status. A significant number of Sars-CoV-2 positive patients exhibited severe to moderate strokes based on the NIHSS classification. Following treatment, the majority of these patients experienced moderate to severe disabilities.  The results of this study enhance our understanding of the relationship between stroke incidence and current or prior infections with SARS-CoV-2.